KOMPENSASI DAN DISIPLIN KERJA DAMPAKNYA TERHADAP KINERJA KARYAWAN PT BANK BJB CABANG PANDEGLANG - Muhammad Saleh; Ardi Hidayat; Efi Tajuroh Afiah (LP2M Universitas Bina Bangsa, 2023)
Human resources is the most decisive factor in achieving company goals. Because, human resources including elements of the power competitive of the nation, for that human resources are required to be superior and professional in its work for the progress and achievement of corporate goals. The purpose of this study was to determine the effect of compensation and work discipline on the performance of employees of PT. bank bjb Pandeglang branch either partially or simultaneously. The method in this study is a quantitative method with the population in this study being all employees of the business section of pt bank bjb as many as 30 people. The sampling method uses a saturated sample technique, so that the entire population is sampled. Based on the results of multiple linear regression analysis, namely Y = 28.336 + 0.838X1 + 0.011X2. The results of the first t-test obtained tcount of 0.206 < ttable 1.703 and a significance value (0.838> 0.05), it can be concluded that partial compensation has no effect on performance. The second t value is obtained by tcount of 2,730 > ttable of 1,703 and a significance value (0.011 < 0.05) so it can be concluded that work discipline has an effect on performance. The results of the f-test simultaneously obtained fcount of 4.419 > ftable 3.51 with a significance value of (0.022 <0.05) it can be concluded that compensation and work discipline simultaneously affect employee performance. the result of the correlation coefficient test simultaneously is 0.497. This value indicates that the effect of compensation and work discipline on employee performance has a moderate relationship